Pengembangan Media Pembelajaran dan Game Interaktif Bagi Anak Berkebutuhan Khusus - yusran, yusran; Revita, Elinda (STKIP PGRI Sumatera Barat, 2021)
Learning media is a communication intermediary between teachers and students that is tailored to the needs, meaning that the teaching and learning process in Special Schools (SLB) must be like what learning materials will provide. The use of media is very important for the success of learning for Children with Special Needs (ABK), for example in the SLB school located in the duo koto agung river, Dharmasraya district, where until now the teaching staff is still using the conventional way of teaching in front of the class for children who have disabilities. different special needs. Methods In designing this interactive media, researchers conducted an initial investigation into the object's school to determine the needs and adjustments of the media to be designed. After conducting interviews with the principal and educators and discussing between the chairperson and members, then at this stage the results of the problems determined are then analyzed again to obtain goals or results that are in accordance with the needs of interactive media for children with special needs in this learning activity. It is hoped that the results of the design of interactive media for children with special needs can help teachers deliver learning materials, and for children with special needs to be able to understand the material presented and increase the enthusiasm for learning for students who understand their shortcomings.